2019
DOI: 10.1186/s13014-019-1397-7
|View full text |Cite|
|
Sign up to set email alerts
|

Normofractionated stereotactic radiotherapy versus CyberKnife-based hypofractionation in skull base meningioma: a German and Italian pooled cohort analysis

Abstract: BackgroundThis retrospective German and Italian multicenter analysis aimed to compare the role of normofractionated stereotactic radiotherapy (nFSRT) to CyberKnife-based hypofractionated stereotactic radiotherapy (CK-hFSRT) for skull base meningiomas.MethodsOverall, 341 patients across three centers were treated with either nFSRT or CK-hFSRT for skull base meningioma. Treatment planning was based on computed tomography (CT) and magnetic resonance imaging (MRI) following institutional guidelines. Most nFSRT pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 53 publications
2
8
1
Order By: Relevance
“…We confirmed that radiosurgery with Gamma, Tomo, and CK is effective and safe in controlling most intracranial meningiomas. The crude radiographic control rate was 96%, which agrees with other series using different schemes of radiosurgery [4,[21][22][23][24][25][26] at the same time interval of follow-up, and complications were mainly mild in less than 10% of the series.…”
Section: Discussionsupporting
confidence: 88%
“…We confirmed that radiosurgery with Gamma, Tomo, and CK is effective and safe in controlling most intracranial meningiomas. The crude radiographic control rate was 96%, which agrees with other series using different schemes of radiosurgery [4,[21][22][23][24][25][26] at the same time interval of follow-up, and complications were mainly mild in less than 10% of the series.…”
Section: Discussionsupporting
confidence: 88%
“…From a similar study where CKRT outcome was assessed on the skull base meningiomas, 1-, 3-, and 10-year LCR were 99.4, 96.8, and 80.3% respectively, which was comparable to our results. [1] Other study on intracranial meningiomas showed 2 year LCR of 81%, which was a bit lower than ours (93.8%). [8] On the other hand, gamma knife radiation surgery (GKS) on the sellar and parasellar meningiomas showed LCR of 98%, 88%, and 82% at 3-, 5-, and 10-year respectively.…”
Section: Radiological Outcome Of Ckrtcontrasting
confidence: 75%
“…[15,1] Although many reports exist regarding on the gamma knife radiation treatment, few large series reports regarding on the CyberKnife radiation treatment (CKRT) exist. [1] CyberKnife is a robotic frameless radiosurgery system equipped with real-time imaging guidance, which can deliver non-surgical multisession stereotactic treatments and automated targeting correction with sub-millimeter accuracy. [4,3] Here we report our facility's outcome of CKRT on the central skull base meningiomas (CSMs).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment decision-making algorithm proposed during the COVID-19 pandemic is given in Figure 1. The suggested treatment options for brain tumours [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] are enlisted in Table 1.…”
Section: Specific Scenariosmentioning
confidence: 99%